CONTEXTUAL BASED MODULE: IMPLEMENTATION ON CRITICAL THINKING SKILLS - Gunawan, Gunawan; Putri, Sabrina Aristya; Untarti, Reni; Kusuma, Jaka Wijaya (International Journal of Multidisciplinary Research and Literature, 2022)
This study aims to produce a contextual-based module to improve students' mathematical critical thinking skills on whole numbers and fractions that have aspects of validity, practicality, and effectiveness. The subjects used were seventh-grade junior high school students. The type of research is research and development (R&D). The development model is ADDIE, consisting of analysis, design, development, implementation, and evaluation stages. Instruments include questionnaires and tests. Data analysis includes aspects of validation, practicality, and effectiveness. The results showed that the contextual-based mathematics module fulfilled the essential elements, namely valid and practical. In addition, the contextual-based module can be used to develop students' mathematical critical thinking skills (effectively).